Determining Child-Friendly Villages as Thematic Tourism Villages: (Case Study: Lamongan Regency) - Yusuf, Mimin A.; Qahar, Dhiah Agustina; Setiadi, Amos; Heriyanto, Muhil (RUAS, 2024)
The Child-Friendly Village Program (DRA) in Lamongan Regency is a continuation of both the Child-Friendly Regency program and the Habitat Agenda II, specifically the Child-Friendly City initiative. Although Lamongan Regency lacks a designated DRA village, several villages have demonstrated commitment and progress in meeting the DRA indicators. In line with the priority program, namely tourist villages, DRA needs to be studied as a thematic tourism village because it has specific tourist attractions and attractions for children. This research aims to determine potential villages for thematic tourism based on Child-Friendly Villages. This study uses a case study method. We collected data through in-depth interviews and observation techniques. The data analysis employs a weighting technique (scoring) to evaluate tourism potential and DRA implementation. This technique involves assigning a score of 86-100 for very good, 71-85 for good, 56-70 for quite good, and less than 55 for not good. The results of the study show that the potential village with the highest value is Kendal Sekaran Village. This research provides practical recommendations for local governments in the development of child-friendly thematic tourism villages, as well as being a reference for other villages in meeting the Child-Friendly Village indicators.